2017
DOI: 10.1007/s11356-017-0349-8
|View full text |Cite
|
Sign up to set email alerts
|

Studies on acute and chronic toxicity of cadmium to freshwater snail Lymnaea acuminata (Lamarck) with special reference to behavioral and hematological changes

Abstract: Molluscs have long been regarded as promising bioindicator and biomonitoring subjects for heavy metals as molluscs are highly tolerant to heavy metals and exhibit high accumulation in their body. In spite of several previous studies about the impact of cadmium on molluscs, little information exists in literatures concerning the toxic effects of cadmium on Lymnaea acuminata, especially pertaining to behavioral and hematological changes as these are considered effective bioindicators and biomonitoring variables … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 32 publications
0
6
0
1
Order By: Relevance
“…Slight differences between the actual and nominal concentrations are likely due to solubility of the metal salts utilized, sorption of metals to treatment containers, or operator error when conducting the assay. The treatment concentrations used in this study were within or below those used in prior trace metal exposure studies with freshwater snails (Ansaldo et al, 2009; Dhara et al, 2017; Gomot, 1998; Pyatt et al, 2002; Ravera, 1977; Sawasdee & Köhler, 2010). While many of the treatments used for this study were higher than the average contamination rates observed in aquatic environments, they can be applied to circumstances dealing with acute contamination events (spills, releases, etc.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Slight differences between the actual and nominal concentrations are likely due to solubility of the metal salts utilized, sorption of metals to treatment containers, or operator error when conducting the assay. The treatment concentrations used in this study were within or below those used in prior trace metal exposure studies with freshwater snails (Ansaldo et al, 2009; Dhara et al, 2017; Gomot, 1998; Pyatt et al, 2002; Ravera, 1977; Sawasdee & Köhler, 2010). While many of the treatments used for this study were higher than the average contamination rates observed in aquatic environments, they can be applied to circumstances dealing with acute contamination events (spills, releases, etc.…”
Section: Discussionmentioning
confidence: 90%
“…Slight differences between the actual and nominal concentrations are likely due to solubility of the metal salts utilized, sorption of metals to treatment containers, or operator error when conducting the assay. The treatment concentrations used in this study were within or below those used in prior trace metal exposure studies with freshwater snails (Ansaldo et al, 2009;Dhara et al, 2017;Gomot, 1998;Pyatt et al, 2002;Ravera, 1977;Sawasdee & Köhler, 2010).…”
Section: Discussionmentioning
confidence: 97%
“…Molluscs are important environmental bioindicators because they accumulate pollutants (Dhara et al, 2017), but aquatic snails are also a key host for parasites that can affect humans, domestic animals, and wildlife, such as trematodes (flatworms) that cause the harmful disease known as schistosomiasis (Gryseels et al, 2006). The trematode life cycle is very complex with multiple intermediate hosts (Sukhdeo, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The ciliary movements are modulated by serotonergic mechanisms originating from the central (pedal) neurons (Sidorov and Kazakevich 2001; Pavlova 2010), while the foot muscle contractions are under dopaminergic regulation (Pavlova 2013, 2019). The spontaneous locomotion of Lymnaea can easily be monitored and quantified (Pyatt et al 2002; Dhara et al 2017; Ford et al 2018).…”
Section: Introductionmentioning
confidence: 99%